Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.21037/mhealth.2019.09.08
|View full text |Cite
|
Sign up to set email alerts
|

The mHealth in the canine assisted therapy: the proposal of a conceptual model for the wearable monitoring

Abstract: An example is the European Convention on Pet Rights promulgated in Strasbourg on 13 November 1987 (https:// rm.coe.int/168007a67d) with profoundly innovative characteristics, which introduces, through a series of articles, regulations aimed at providing a complete legal structure to protect all pet animals which are finally recognized for their importance in terms of quality of life and value for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Several studies have shown that pets are valid support during strong emotional stress [23][24][25][26]. However, it has been reported the importance of objectively quantifying such a positive pet-owner interaction [16,17] to overcome emotional distress [27]. The eS developed and presented herein has been promptly submitted through modern communication Apps, to 4993 subjects, receiving almost all responses within 6 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that pets are valid support during strong emotional stress [23][24][25][26]. However, it has been reported the importance of objectively quantifying such a positive pet-owner interaction [16,17] to overcome emotional distress [27]. The eS developed and presented herein has been promptly submitted through modern communication Apps, to 4993 subjects, receiving almost all responses within 6 days.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism which explains the positive effect of the owner-pet interaction is currently under study; however, some studies suggested that these positive effects can depend on (a) the encouragement to do physical activity while walking the dog and (b) the co-presence of a pet [14,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The mHealth in the canine assisted therapy: the design and application of a kit for the wearable monitoring during a walking session position of the pet, the approach must be revised in a more general and bidirectional approach embedding the assessment of the health benefits contemporary for the two actors, human and pet (8). Among the most commonly used types of AAT there is the canine assisted therapy (CAT).…”
Section: Original Articlementioning
confidence: 99%
“…Consequently, it enhances production efficacy, guarantees the exportation of products, and upholds public health and safety [ 1 ]. For pet owners, monitoring physiological information about pets can help owners monitor their pets’ health issues more quickly, enhance diagnosis and treatment effectiveness [ 2 ]. In the realm of animal research, researchers are capable of grasping information about animal metabolism, and the neurological system, further providing crucial references for researching human diseases.…”
Section: Introductionmentioning
confidence: 99%